Elicitors and phenotypes of adult patients with proven IgE‐mediated food allergy and non‐immune‐mediated food hypersensitivity to food additives. Issue 11 (10th August 2022) - Alexiou, Aikaterina; Höfer, Veronika; Dölle‐Bierke, Sabine; Grünhagen, Josefine; Zuberbier, Torsten; Worm, Margitta
Abstract: Background: Food allergy is a growing health concern with a prevalence of 2%–3% in the adult population in Europe. Non‐immune‐mediated food hypersensitivities, which include reactions after ingestion of food additives, affect 1% of adults and may resemble IgE‐induced allergic reactions without identifiable immunologic sensitization. A double‐blind placebo‐controlled food challenge (DBPCFC) is the gold standard for the diagnosis of any food hypersensitivity. Objective: We analysed a large group of adult patients with suspected food hypersensitivity, who had undergone DBPCFC, to better understand IgE‐mediated food allergy and non‐immune‐dependent food hypersensitivity to food additives in adults regarding elicitors, symptoms and positivity rates of oral challenges. Methods: Data from 541 patients with suspected food hypersensitivity were analysed, who underwent an oral food challenge between 2010 and 2019. Results: IgE‐dependent food allergy was confirmed in 114 of 329 adult patients (34.6%). The confirmation rate was lower in the group of patients with suspected non‐immune‐mediated reactions to food additives (65 of 286, 22.7%). Urticaria and angioedema appeared more frequently in patients with IgE‐mediated food allergies. By contrast, flush and diarrhoea were the most frequent symptoms after a challenge in the group with the non‐immune‐mediated reactions to food additives. Wheat and celery were the most frequently identified food allergens in adults, whereas colourings and preservatives were the most frequent elicitors of non‐immune‐mediated food hypersensitivity. Conclusion: The importance of oral food challenges for the diagnosis of food hypersensitivity is confirmed. IgE‐dependent food allergy is more frequently proven, reaching a positivity rate of one‐third and only about 20% for non‐immune‐mediated hypersensitivity. Future studies should elaborate on the mechanisms of non‐immune‐mediated food hypersensitivity and the clinical impact of cofactors in this setting.